The Effect of Price Perception, Digital Promotion, and E-WOM on Consumer Satisfaction Maxim Palu - Gunawan Gunawan; Rosida P. Adam; Zakiyah Zahara; Muh. Riswandi Palawa (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to analyze the influence of price perception, digital promotion, and electronic word of mouth (E-WOM) on consumer satisfaction with Maxim online motorcycle taxi services in Palu City. The research seeks to identify the dominant factors affecting consumer satisfaction in the competitive online transportation market. Methodology/approach: A quantitative method was applied using a questionnaire distributed to 65 respondents who had used Maxim services at least once. The sampling technique was incidental sampling. Data were analyzed using multiple linear regression with SPSS 25, preceded by validity, reliability, and classical assumption tests to ensure data feasibility. Results/findings: The findings reveal that price perception and digital promotion exert a negative but insignificant impact on consumer satisfaction, whereas electronic word of mouth (E-WOM) demonstrates a positive and significant influence. This indicates that online reviews and recommendations contribute more substantially to consumer satisfaction compared to pricing or promotional efforts. Collectively, these three variables account for 17% of the variation in consumer satisfaction levels. Conclusions: Consumer satisfaction with Maxim services in Palu City is primarily driven by E-WOM rather than pricing or digital promotion factors, highlighting the importance of digital interaction and customer feedback in building satisfaction. Limitations: This study was limited to respondents in Palu City; future research should include broader areas and additional factors such as service quality or brand image. Contribution: The findings provide managerial insight for Maxim to strengthen online engagement and digital reputation management to enhance customer satisfaction.